Unusual Findings of Human-Associated Four-Nucleated Entamoeba Species in Captive Wild Animals - Lorena Esteban-Sánchez; Juan José García-Rodríguez; Francisco Ponce-Gordo (Animals, 2025)
Several species of amoebae in the genus Entamoeba forming four-nucleated mature cysts are pathogenic, but their identification is challenging due to a lack of distinctive morphological traits. Furthermore, host species cannot reliably be used as a criterion for identification. In this study, several isolates of four-nucleated cyst-forming Entamoeba species from animals at the Zoo Aquarium of Madrid are genetically identified. Entamoeba cysts were identified through microscopic analysis of faecal samples; none of the animals exhibited symptoms. DNA was extracted, and a fragment of the SSU-rRNA gene was PCR-amplified and sequenced to identify the species. Entamoeba dispar was identified in mantled guerezas (Colobus guereza), lar gibbons (Hylobates lar), greater rheas (Rhea americana) and giant anteaters (Myrmecophaga tridactyla). Entamoeba hartmnanni was detected in mandrills (Mandrillus sphinx) and chimpanzees (Pan troglodytes). Entamoeba nuttalli was detected in mandrills; the analysis of sequences available in GenBank revealed that this species has also been detected in human samples. The identification of the Entamoeba species across diverse host species underscores the need for genetic confirmation to prevent misidentifications. These findings expand the known host range of these species and emphasize the importance of regular monitoring to minimize transmission risks, including potential cross-species transmission to/from humans.